INTELLECTUAL PROPERTY LAW IN THE PRACTICE OF SUBSURFACE USE - Amangeldy , Айжан Амангелдіқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
This article is devoted to the study of the relationship of intellectual property rights with the right of subsurface use. Currently, in the field of subsoil use, there has been a powerful development and introduction of innovative technologies into the production processes of the fuel and energy complex. The sphere of subsurface use has always required the use of high technologies in order to generate more income and minimize the harmful impact on the environment. In the article, the author made an attempt to reveal the legal nature of geological information, offered his author's vision on the issue of attributing geological information to the number of objects of intellectual property rights. The complexity of obtaining the results of the study lies in the fact that geological information is contained not only in natural media (drill cores, samples of minerals, carbon dioxide, mercaptans, water, samples of rocks and minerals, samples and collections of stone material, slates, anshlifs, mineral solutions and powders), but also artificial media that they are the result of intellectual work (journals, tests, analyses, observations, geological reports, reports on the results of geological exploration, reports on the assessment of resources and mineral reserves, etc.). In addition, in the legislation of the Republic of Kazakhstan (hereinafter - RK), the regime of ownership rights is extended to geological information, which is a consequence of insufficient study of geological information as an object of rights. The article shows the relationship of relations in the field of subsoil use with copyright, since many processes are based on the use of computer programs, information systems and other software. In addition, the activities of subsurface users are inextricably linked with inventions – objects of patent law, starting with geological exploration, survey work and ending with mining. The connection between the means of individualization and subsurface users is also obvious, since each subsurface user acts in civil circulation under its own brand name, produces products under a trademark or service mark. In addition, subsoil users often violate the exclusive rights of copyright holders, which leads not only to litigation, but also to losses in the case of the use of counterfeit goods.